2012
DOI: 10.1007/s00066-012-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory gated [18F]FDG PET/CT for target volume delineation in stereotactic radiation treatment of liver metastases

Abstract: FDG-PET can distinguish vital tumor tissue and scar tissue, and therefore alters the GTV especially in patients with previous local treatment. In addition, it reduces the interobserver variability significantly compared to MRI. However, respiratory gated PET is necessary for good co-registration of PET and MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Multi-modality imaging techniques including MRI and PET/CT have been used for SBRT of liver metastases (3,4). PET/CT imaging provides biologic information on the tumor and has proved useful for staging, surveillance, and radiation treatment planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-modality imaging techniques including MRI and PET/CT have been used for SBRT of liver metastases (3,4). PET/CT imaging provides biologic information on the tumor and has proved useful for staging, surveillance, and radiation treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, utilization of PET/CT imaging may improve target delineation for liver metastases compared to MRI (4). In addition, two planning studies have suggested that 4D PET/CT may provide added benefit for liver SBRT planning and target delineation compared to non-gated PET/CT imaging (4,11).…”
Section: Discussionmentioning
confidence: 99%
“…The value of anatomic-biologic tumor targeting achieved with PET/CT in the radiotherapy planning process has been clearly defined in lung, head, and neck malignancies as well as lymphoid neoplasms (8)(9)(10). Published data also suggest improvements in the imaging of esophageal, cervical, and rectal cancers (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, application of even high tumoricidal doses can be applied safely and non-invasively by stereotactic body radiotherapy (SBRT), intensity-modulated RT (IMRT) or even particle beam therapy (PBT) [11][12][13][14][15][16][17][18][19][20][21]. Many reports over the last years have shown favourable local control rates after radiosurgery or hypofractionated RT in liver metastases or even small primary liver tumors with an advantageous toxicity profile [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%